Guided wave propagation and scattering for structural health monitoring of stiffened composites. (15th January 2018) - Memmolo, V.; Monaco, E.; Boffa, N.D.; Maio, L.; Ricci, F.
Abstract: Impact induced damages in stiffened composite structures are usually settled with constrained design criteria and recurring maintenance tasks, that affect weight savings potentialities of composite materials as well as operative costs. To overcome those penalties due to hidden damages, this paper deals with detection, localization and size assessment of stringers disbondings with monitoring techniques by permanently attached piezoelectric transducers (PZT) capable to excite and sense guided ultrasonic waves. A composite stiffened plate typically designed for wingbox structures is investigated to test a novel detection technique capable to predict arrival time of guided waves scattered from stringers detecting, as a consequence, any possible change in a specific scattering area. Theoretical aspects are investigated to correctly exploit the technique leading to a geometrical reduction which returns the optimal configuration of sensors. Several measurements are carried out to validate the hypothesis and the approach effectiveness. A promising result in agreement with state-of-the-art ultrasonic nondestructive testing is thus obtained and discussed. Furthermore it is shown that processing Lamb wave reflections signals is possible to improve the localization accuracy respect to a general purpose reconstruction algorithm while making use of fewer number of sensors possible.